Fusion porphyrin axial modification Ti < 3 > C < 2 > T < x > nonlinear optical nano hybrid material as well as preparation and application thereof

By forming covalent connections with the Ti3C2Tx nanosheets, the problems of insufficient binding force and poor stability of the existing Ti3C2Tx materials are solved, and its nonlinear optical performance and application range are significantly improved.

CN119241569AActive Publication Date: 2025-01-03TONGJI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411120243.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-01-03
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The non-covalent modification binding force of existing Ti3C2Tx nonlinear optical materials is insufficient, the stability is poor, the non-linear optical properties of electrochemical regulation are dynamic and are not conducive to practical application, and the research on covalent functionalization has not been fully explored.

Method used

By forming coordination bonds between the fusion porphyrin and nitrogen atoms on the surface of Ti3C2Tx nanosheets, the diazo brine solution is modified with potassium iodide to form a stable covalent connection, expanding the electronic structure and chemical structure of the material and improving the nonlinear optical absorption performance .

Benefits of technology

It significantly enhances the optical limiting effect of the material at 532nm and 800nm, improves the overall nonlinear optical performance, broadens the application range, and provides stable structure and performance, suitable for production and processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241569A_ABST
    Figure CN119241569A_ABST
Patent Text Reader

Abstract

The invention relates to a fusion porphyrin axial modification Ti < 3 > C < 2 > T < x > nonlinear optical nano-hybrid material as well as preparation and application thereof. The nano-hybrid material is obtained by enabling fusion porphyrin to form a coordinate bond through a zinc atom at the ring center and a nitrogen atom covalently connected to a pyridine ring on the surface of a Ti < 3 > C < 2 > T < x > nanosheet. Compared with a single functional component, the nano hybrid material TFP-Ti3C2Tx shows a remarkably enhanced optical limiting effect under nanosecond pulsed light with the wavelength of 532 nm and femtosecond pulsed light with the wavelength of 800 nm. According to the invention, a surface chemical modification strategy of titanium carbide MXene is developed, and the obtained nano hybrid material shows time domain and spectral domain crossing optical limiting performance and has the potential of being applied to modern photon or optoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to organic-inorganic functional composite materials and military high-intensity laser protection materials, and relates to a fused porphyrin axially modified Ti3C2T x Nonlinear optical nanohybrid materials and their preparation and applications. Background Art

[0002] Nonlinear optical (NLO) materials have been widely used in various fields, including electronic communications, all-optical data processing, optical switches, data storage, bioimaging, quantum information technology, etc. Nonlinear optical materials are currently receiving much attention in scientific research. In the past few decades, different types of nonlinear optical materials such as semiconductors, organic molecules, inorganic glasses and crystals, and nanomaterials have been widely studied. The development of new materials with strong optical nonlinear properties and ultrafast response times has always been a research hotspot. Among them, two-dimensional materials such as graphene, transition metal sulfides, and black phosphorus nanosheets have attracted attention due to their good nonlinear optical properties. As an emerging two-dimensional material, MXenes materials have attracted great attention in the fields of optics, energy storage, and catalysis due to their high conductivity, tunable band gap, and ultrafast carrier dynamics. MXene is prepared from transition metal carbides, nitrides, or carbonitrides with MAX phases. By etching the A layer with HF or HCl / LiF solution, a few-layer MXenes nanosheet structure can be obtained. The general expression formula of MXenes is M n+1 X n T x , where M represents transition metal elements, such as titanium, molybdenum and vanadium; X represents carbon, nitrogen or a mixture of the two; T refers to the functional groups carried on its surface, such as -OH, =O and -F. Recent studies have shown that MXenes have the potential to be used as high-performance nonlinear optical materials. The most widely studied Ti3C2T x For example, Jiang et al. studied Ti3C2T x In the near-infrared region (800-1800nm), the nonlinear optical properties show a huge nonlinear absorption coefficient of 10-13esu. Dong and his colleagues used interfacial film formation technology to prepare uniform and variable thickness two-dimensional Ti3C2T x The film shows thickness-dependent saturation absorption behavior at 1064nm. As the film thickness increases, the saturation intensity of the material decreases and the modulation depth increases.

[0003] In order to further optimize and improve Ti3C2T x Researchers have proposed some feasible and effective research strategies for the optical nonlinearity of Ti3C2T xNon-covalent modification, that is, some functional materials with nonlinear optical response are combined with Ti3C2T through non-covalent interaction (van der Waals force) x It has been reported that BP, Fe3O4 nanoparticles and Ag nanoparticles can be successfully loaded onto Ti3C2T x Recently, Huang et al. reported the electrochemical regulation of Ti3C2T x The nonlinear optical response of Ti3C2T at different wavelengths. x The functional groups on the surface can be converted between -OH-rich and =O-rich, and the corresponding nonlinear optical performance (saturated absorption or anti-saturated absorption) will also change accordingly. However, the existing control methods inevitably have certain limitations. On the one hand, the binding force between the two components of the non-covalent interaction is weak, making it difficult to produce an efficient charge transfer process, and the van der Waals stacked complex has poor stability during solution processing and its structure is easily destroyed. On the other hand, the change in nonlinear optical properties caused by electrochemical treatment is actually a "dynamic change", that is, when the external electric field disappears, the resulting nonlinear optical properties will also disappear. Therefore, electrochemical control is not suitable for Ti3C2T x On the contrary, covalent functionalization can form a strong covalent bond between the two components. This form not only ensures an efficient charge transfer process at the closely connected hybrid interface, but also the stable hybrid material structure is not easily destroyed by external forces, ensuring the stability of the structure and performance and meeting the requirements of production and processing. x Covalent modification work in important fields such as field effect transistors, smart sensors and supercapacitors has been reported. x The study of photophysical properties and nonlinear optical properties of organic functional molecules has not been fully explored. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a fused porphyrin axially modified Ti3C2T x Nonlinear optical nanohybrid materials and their preparation and application. The prepared organic-inorganic covalent nanohybrid materials combine fused porphyrin and Ti3C2T x The electronic and chemical structure characteristics of the nanosheets improve the nonlinear optical absorption performance of the material and broaden the scope of application of the material's nonlinear optics.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In a first aspect, the present invention provides a fused porphyrin axially modified Ti3C2T x Nonlinear optical nanohybrid material composed of fused porphyrin covalently linked to Ti3C2T via a zinc atom in the ring center x The nitrogen atoms on the pyridine ring on the surface of the nanosheet form coordination bonds.

[0007] In a second aspect, the present invention also provides a fused porphyrin axially modified Ti3C2T x The method for preparing a nonlinear optical nano-hybrid material comprises the following steps:

[0008] (1) Take a few layers of titanium carbide Ti3C2T x The nanosheets were dispersed in deionized water, and pyridine diazonium salt aqueous solution and potassium iodide were added in an ice bath. After the reaction, the Ti3C2T3C2T3 nanosheets covalently modified with pyridine on the surface were obtained by separation. x Nanosheets, denoted as Py-Ti3C2T x ;

[0009] (2) Take the obtained Py-Ti3C2T x Dispersed in DMF, then added with fused porphyrin TFP, heated to reflux, and separated to obtain fused porphyrin axially modified Ti3C2T x Nanosheets, namely the target product TFP-Ti3C2T x .

[0010] Further, in step (1), the Ti3C2T x The mass ratio of the nanosheets, pyridine diazonium salt and potassium iodide is 50 mg: (450-550) mg: (0.8-1.2) g, preferably 50 mg: 500 mg: 1 g.

[0011] Furthermore, in step (1), the pyridine diazonium salt aqueous solution is prepared by the following method:

[0012] Sodium nitrite and 4-aminopyridine were dissolved in water and hydrochloric acid respectively, and the obtained sodium nitrite aqueous solution and 4-aminopyridine hydrochloric acid solution were cooled to 0° C. in an ice bath;

[0013] A sodium nitrite aqueous solution cooled to 0° C. is added dropwise to a 4-aminopyridine hydrochloric acid solution to react to obtain a light yellow solution, which is a pyridine diazonium salt aqueous solution.

[0014] Furthermore, the ratio of the amount of sodium nitrite to water added is (1.2-1.3) g:7 mL;

[0015] The ratio of the added amount of 4-aminopyridine to the amount of hydrochloric acid is (1.5-1.7) g:5 mL, and the concentration of the hydrochloric acid is 4 mol / L;

[0016] The mass ratio of sodium nitrite to 4-aminopyridine is (1.2-1.3):(1.5-1.7).

[0017] Furthermore, in step (2), Py-Ti3C2T x The mass ratio of tantalum to TFP is 1:3-5, preferably 1:4.

[0018] Furthermore, in step (2), the heating reflux temperature is 115-125°C, preferably 120°C.

[0019] Furthermore, in step (2), the heating reflux time is 18 to 30 hours, preferably 24 hours.

[0020] Furthermore, in step (2), heating under reflux is carried out under a nitrogen atmosphere.

[0021] In a third aspect, the present invention provides a fused porphyrin axially modified Ti3C2T x Application of nonlinear optical nanohybrid materials as nonlinear optical materials.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The present invention uses diazonium salt to treat Ti3C2T x The free radical addition reaction and the coordination effect of nitrogen atoms and metal atoms were used to axially covalently modify the fused porphyrin molecules onto Ti3C2T for the first time. x Surface. The present invention expands the surface chemistry of titanium carbide MXene and enriches the design and preparation strategies of binary nanohybrid materials based on titanium carbide MXene.

[0024] 2. Nano-hybrid material TFP-Ti3C2T prepared by the present invention x The lateral surface plasmon resonance signal from the MXene component in its UV-visible-near-infrared absorption spectrum underwent a significant shift, proving that there is a strong electronic interaction between the fused porphyrin molecules and the two-dimensional nanosheets.

[0025] 3. TFP-Ti3C2T prepared by the present invention x The nanohybrid material exhibits significantly enhanced optical limiting effect under 532nm nanosecond excitation light and 800nm ​​femtosecond excitation light compared with single-component TFP and pure nanosheets. x The coupling between nanosheets plays an important role in improving the overall nonlinear optical properties of the material. This hybrid system design idea will be of great significance for the synthesis and preparation of more Ti3C2T x The binary nonlinear optical functional materials based on this method have reference significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The TFP-Ti3C2T prepared by the present invention x Preparation routes of nanohybrid materials;

[0027] Figure 2 The TFP-Ti3C2T prepared by the present invention x Nano-hybrid materials and their precursor materials, Ti3C2T x Infrared spectrum;

[0028] Figure 3 The TFP-Ti3C2T prepared by the present invention x X-ray diffraction patterns (XRD) of nanohybrid materials and their precursor materials;

[0029] Figure 4 The TFP-Ti3C2T prepared by the present invention x X-ray photoelectron spectroscopy (XPS) of nanohybrid materials;

[0030] Figure 5 The TFP-Ti3C2T prepared by the present invention x Nano-hybrid materials and their precursor materials Ti3C2T x Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images;

[0031] Figure 6 The TFP-Ti3C2T prepared by the present invention x UV absorption spectra of nanohybrid materials and precursor materials;

[0032] Figure 7 The TFP-Ti3C2T prepared by the present invention x Z-scan spectra of nanohybrid materials and precursor materials at 800nm ​​wavelength;

[0033] Figure 8 The TFP-Ti3C2T prepared by the present invention x Z-scan spectra of nanohybrid materials and precursor materials at a wavelength of 532 nm. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0035] The raw materials in the following examples are all from reagent companies such as Exploration Platform, Anaiji, and Bailingwei. The synthesis method of fused porphyrin is referenced from the literature (Ostrowski, S., Grzyb, S. (2012). Direct β-amination reaction in porphyrin systems-a simple route to compounds containing two nitrogensubstituents at both β-positions of the same pyrrole unit. Tetrahedron Letters, 53 (47), 6355-6357.)

[0036] The rest of the raw materials, products or processing techniques, unless otherwise specified, are conventional commercially available products or conventional processing techniques in the art.

[0037] Embodiment 1:

[0038] Reference Figure 1 The process flow shown in the figure provides a Ti3C2T ... x Preparation method of nano-hybrid materials:

[0039] first step:

[0040] 1g Ti3AlC2 was added to a mixture of 20mL containing 9M HCl solution and 1g lithium fluoride in multiple batches, and the suspension was stirred continuously at 40°C for 24 hours. Then, the crude product after the reaction was washed with deionized water and centrifuged at 8000rpm for 5 minutes, and the above process was repeated several times until the pH of the supernatant reached 6. Deionized water was added to the centrifuged precipitate and ultrasound was continued for 1 hour. The resulting dispersion was then centrifuged at 3500rpm for 45 minutes, the supernatant was collected, and deionized water was continued to be added to the remaining precipitate to repeat the above process 2 to 3 times. Finally, 350mg black Ti3C2T was prepared by freeze-drying the supernatant. x Nanosheets.

[0041] Step 2:

[0042] 1.23 g NaNO2 and 1.6 g 4-aminopyridine (4-AP) were dissolved in 7 mL H2O and 5 mL 4M HCl, respectively, and then the system was cooled to 0°C in an ice bath. The above NaNO2 aqueous solution was added dropwise to the hydrochloric acid solution of 4-AP, and the resulting light yellow solution (i.e., pyridine diazonium salt aqueous solution) was maintained at 0°C in an ice bath and stirred for 30 minutes.

[0043] Then, 100 mg Ti3C2T xThe nanosheets were dispersed in 100 mL of deionized water, and after ultrasonic dispersion, the dispersion was added dropwise to the pyridine diazonium salt aqueous solution and the temperature was kept at 0°C to prevent the decomposition of the diazonium salt. After the reaction system reacted at 0°C for 3 hours, 1 g of potassium iodide was added and stirred at room temperature for 15 hours. The reaction solution was filtered with a filter membrane with a pore size of 0.22 μm, and the resulting black solid was dispersed in DMF for multiple ultrasonic-filtration-redispersion processes to ensure that unreacted organic small molecules and other reaction by-products were completely removed. After drying at 80°C in a vacuum oven for 24 hours, pyridine surface-modified Ti3C2T x Nanosheets (Py-Ti3C2T x ).

[0044] Step 3:

[0045] The reaction was carried out under nitrogen atmosphere. 50 mg Py-Ti3C2T x Place it in a round-bottom flask equipped with a reflux condenser, then add 50mL DMF and ultrasonicate for 1 hour. Subsequently, add 200mg TFP to the above reactants, and stir the reaction system at 120°C for 24 hours. After the reaction is completed and cooled to room temperature, the reaction solution is filtered through a filter membrane with a pore size of 0.22μm, and the filtered filter cake is washed several times with organic solvents such as DMF, tetrahydrofuran and dichloromethane until the absorption spectrum signal of the fused porphyrin is no longer detected in the final filtrate. The filter cake is placed in a vacuum drying oven at 80°C and dried for 24 hours to obtain the final product (TFP-Ti3C2T x ).

[0046] Figure 2 The prepared nano-hybrid material TFP-Ti3C2T x and infrared spectra of precursor materials. First, we focus on Ti3C2T x Sample, located at 3601 and 1462 cm -1 The absorption peak at 1664cm can be attributed to the stretching and bending vibration modes of -OH. -1 The absorption peak at 500 to 800 cm -1 The wavelength range includes the vibration modes of Ti-OH, Ti-O and Ti-C bonds. x After the nanosheets were modified with diazonium salt, Py-Ti3C2T x The peak intensity of the stretching vibration of -OH in the high wave number region of the sample infrared spectrum is significantly reduced, indicating that a large amount of hydroxyl groups are consumed during the reaction with pyridine diazonium salt. -1 The new absorption peak observed in the range is caused by the stretching vibration of the pyridine ring (located at 992 cm -1The pyridine ring skeleton vibration at 1529 and 1594 cm -1 It is worth noting that at 2200-2300 cm -1 The wavelength range does not contain N2 + The characteristic stretching vibration peaks of the group indicate that the pyridine group is covalently connected to Ti3C2T x For the TFP sample, the -1 The absorption peaks at 1096 and 1221 cm-1 can be attributed to the NH stretching vibration peaks on the porphyrin ring, and the stretching vibration peaks of the pyrrole CN at the center of the porphyrin ring are located at 1096 and 1221 cm-1, respectively. -1 The above characteristic absorption peaks of porphyrin molecules are also found in TFP-Ti3C2T x The infrared spectrum of the sample was found, indicating that the fused porphyrin was successfully modified on Ti3C2T by axial coordination between the N atom on pyridine and the zinc atom. x surface.

[0047] Figure 3 The prepared nano-hybrid material TFP-Ti3C2T x And X-ray diffraction patterns of precursor materials. For Ti3AlC2 and Ti3C2T x For example, the diffraction peak of the precursor Ti3AlC2 at 39.2° belonging to the (104) crystal plane disappears after etching, and the (002) diffraction peak shifts to a low angle of 6.3°. The above two points indicate that the Al atomic layer is completely removed and the Ti3C2T x Formation of nanosheets. After diazonium salt modification, Py-Ti3C2T x The (002) diffraction peak of Py-Ti3C2T is shifted to 5.6°. For MXene materials, the change in the position of the (002) diffraction peak represents the change in the interlayer spacing, which is closely related to the interlayer insertion of substances. x The expansion of the interlayer distance should be attributed to the introduction of pyridine molecules. x The (002) diffraction peak of the sample further shifts to a lower angle of 5.2°, indicating that the introduction of porphyrin molecules further expands the Ti3C2T x It is worth noting that Py-Ti3C2T x and TFP-Ti3C2T x The (002) diffraction peak of the original Ti3C2T x The strength of the sample is reduced, which may be due to the coverage of surface functional groups disrupting the Ti3C2T x This is due to the stacking structure of the layers along the c-axis.

[0048] Figure 4 The prepared nano-hybrid material TFP-Ti3C2T x X-ray photoelectron spectra of the precursor materials and the precursor materials. It can be seen that there are five peaks centered at 684, 563, 530, 455 and 284 eV in the XPS spectra of the two materials, which are attributed to F1s, Ti 2s, O 1s, Ti 2p and C1s respectively. x The signal of nitrogen element was observed in the Py-Ti3C2T x The chemical bond information between Figure 4 b and 4c respectively give Ti3C2T x and Py-Ti3C2T x The fine spectrum of O1s of Py-Ti3C2T. Both samples show characteristic peaks at around 531.4 and 529.8 eV, which are attributed to Ti-OH and Ti-O. x A new peak appears at 531 eV, which can be attributed to the interaction between porphyrin and Ti3C2T x The newly formed Ti-OC bonds between the nanosheets further prove that the pyridine molecules are covalently linked to the Ti3C2T x The surface is consistent with the infrared spectrum test results. Figure 4 d and 4e show the TFP-Ti3C2T x The XPS full spectrum and the fine spectrum of Zn2p. After the introduction of fused porphyrin, TFP-Ti3C2T x There are two additional areas with a ratio of 2:1, which are respectively attributed to Zn 2p 1 / 2 and Zn 2p 3 / 2 Considering that the only source of Zn element is TFP, this indicates that the TFP component is successfully axially connected to Ti3C2T through pyridine molecules. x surface.

[0049] Figure 5 The prepared TFP-Ti3C2T x Nano-hybrid materials and their precursor materials Ti3C2T x Scanning electron microscopy and transmission electron microscopy images. Figure 5 ac respectively give Ti3C2T x 、Py-Ti3C2T x 、TFP-Ti3C2T x SEM image of the original Ti3C2T xThe materials obtained after functionalization are all irregular ultra-thin nanosheets of a few microns in size. No obvious morphological changes were observed before and after functionalization, indicating that Ti3C2T x The structure of the nanosheets was not destroyed. In order to further explore the surface morphology details of the samples, Figure 5 df gives Ti3C2T x 、Py-Ti3C2T x 、TFP-Ti3C2T x TEM image of the original Ti3C2T x The nanosheets showed a clean and relatively smooth surface, indicating that during the synthesis process, Ti3C2T x The nanosheet surface does not undergo obvious oxidation behavior, and it has a few-layer stacked sheet structure. However, after surface modification, Py-Ti3C2T x and TFP-Ti3C2T x The surface of the hybrid becomes obviously rougher, indicating that the introduced organic molecules and Ti3C2T x The nanosheets interact with each other. Figure 5 g gives TFP-Ti3C2T x Element distribution diagram of nanohybrid materials, except Ti3C2T x In addition to the Ti, C, and O elements contained in the nanosheets themselves, the N and Zn elements from the porphyrin are also evenly distributed on the surface of the hybrid material. This result is the axial modification of the porphyrin to the Ti3C2T x The surface provides additional evidence.

[0050] Figure 6 The prepared TFP-Ti3C2T x Ultraviolet absorption spectra of nanohybrid materials and precursor materials. Pure Ti3C2T x The nanosheets exhibit broadband absorption characteristics from the ultraviolet to the near-infrared region due to their near-zero bandgap energy band structure, and their wide absorption peak at 790nm belongs to the transverse surface plasmon (TSP) resonance peak. The fused porphyrin exhibits characteristic absorption peaks of By (420nm), Bx (576nm) and Qx (1123nm) in the near-ultraviolet, visible and near-infrared regions, respectively. Among them, the two split B bands originate from the exciton coupling effect produced by the Coulomb interaction between the transition dipole moments. At the same time, the triple bond melting connection between the monomeric porphyrins changes the electronic distribution of the porphyrin ring and destroys the degeneracy of the eg orbital, resulting in a significant enhancement and red shift of the Q band absorption. They belong to TFP and Ti3C2T x The characteristic absorption peak also appears in TFP-Ti3C2T xIn the nanohybrid material, it is shown that the organic component TFP is successfully bonded to Ti3C2T through axial connection. x In particular, TFP-Ti3C2T x represents Ti3C2T x The absorption peak of the TSP mode of Ti3C2T4 has obviously blue-shifted (785nm), and the By absorption peak representing TFP has also red-shifted to 423nm. x The absorption peak of the TSP mode is closely related to the free carrier concentration on its surface. x When the surface electron density of TFP-Ti3C2T nanosheets increases, the increase of its surface electron density will cause the blue shift of TSP peak position; conversely, the decrease of its surface electron density will cause the red shift of TSP. x The blue shift of the peak position in the spectrum indicates that the modification of TFP increases the x At the same time, the red shift of the By absorption peak position of TFP indicates the increase of the conjugation degree of porphyrin molecules. The above phenomena together explain the x There is an obvious electron transfer process between them.

[0051] Figure 7 The prepared TFP-Ti3C2T x Z-scan spectra of nanohybrid materials and precursor materials at 800 nm. The pulse width of the incident light is 34 fs and the rereading frequency is 1 kHz. The three groups of samples are also dispersed in DMF and their transmittance at 800 nm is uniformly adjusted to 70%. Figure 7 ac respectively give TFP, Ti3C2T x and TFP-Ti3C2T x Z scan measurement results in the energy range of 50-130nJ. As the input energy increases, all three groups of samples show anti-saturation absorption changes that are dependent on laser energy, and the valley shape of the curve gradually deepens. min Specifically, within the range of 50-130 nJ incident light energy, the T min The values ​​are 0.97, 0.95 and 0.92 respectively, Ti3C2T x T min The values ​​are 0.98, 0.97 and 0.95 respectively. x Nanohybrid materials, which show better performance than pristine TFP and Ti3C2T at different incident laser energies. x Smaller T min The values ​​are 0.94, 0.92 and 0.89 respectively. For a more intuitive comparison, Figure 7d Comparison of TFP, Ti3C2T x and TFP-Ti3C2T x The Z-scan results, obtained from the data fitting of the Z-scan curve, have been included Figure 7 f, the β values ​​of each sample were calculated to be 0.00542 cm GW -1 (Ti3C2T x ), 0.00869cm GW -1 (TFP) and 0.0145 cm GW -1 (TFP-Ti3C2T x ). It can be found that under femtosecond pulse conditions, TFP-Ti3C2T x The nanohybrid material also exhibited the lowest T min value (0.89) and the maximum β value (0.0145 cm GW -1 ), indicating that compared with the original sample, TFP-Ti3C2T x The nonlinear optical properties of nanohybrid materials are significantly enhanced.

[0052] Figure 8 The prepared TPP-Ti3C2T x Z-scan spectra of the nanohybrid material and precursor material at a wavelength of 532 nm. Figure 8 ac respectively give TFP, Ti3C2T x and TFP-Ti3C2T x Z-scan measurement results in the energy range of 50-105 μJ. Under different incident laser excitation intensities, the Z-scan curves of all samples show a symmetrical trough shape, indicating the emergence of a typical anti-saturation absorption phenomenon, which improves the optical confinement of the material to the incident laser. Specifically, for TFP, the T min They are 0.87 at pulse energy of 50 μJ, 0.80 at pulse energy of 75 μJ, and 0.74 at pulse energy of 105 μJ. x Nanosheets, whose focal point is T min They are 0.86 at a pulse energy of 50 μJ, 0.77 at a pulse energy of 75 μJ, and 0.68 at a pulse energy of 105 μJ. x Nanohybrids, whose focal T min They are 0.77 at a pulse energy of 50 μJ, 0.68 at 75 μJ, and 0.56 at 105 μJ, respectively. Figure 8 d Comparison of TFP, Ti3C2T x and TFP-Ti3C2T xThe nonlinear absorption coefficient (β) obtained from the Z-scan curve data fitting has been included in Figure 8 f, the β values ​​of each sample are calculated to be 51.66 cm GW -1 (TFP), 69.66cm GW -1 (Ti3C2T x ) and 130.86 cm GW -1 (TFP-Ti3C2T x ).from Figure 8 It can be clearly seen in e and 8f that TFP-Ti3C2T x Nanohybrid materials have the smallest T min value (0.56) and the maximum β value (130.86 cm GW -1 ).

[0053] The above results show that the modification of TFP can effectively improve the x Nonlinear optical response of nanosheets under nanosecond pulse laser conditions. According to the above Z-scan test results, TFP-Ti3C2T x Nanohybrid materials have better third-order nonlinear performance and show broadband NLO characteristics, which greatly broadens the application range of materials. This method provides new ideas for the future design and preparation of more, more flexible and better-performing nonlinear optical materials and devices.

[0054] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A fused porphyrin axially modified Ti3C2T x Nonlinear optical nanohybrid material, characterized in that It consists of a fused porphyrin covalently linked to Ti3C2T through a zinc atom in the center of the ring. x The nitrogen atoms on the pyridine ring on the surface of the nanosheet form coordination bonds.

2. A fused porphyrin axially modified Ti3C2T as claimed in claim 1 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: The following steps are involved: (1) Take Ti3C2T x The nanosheets were dispersed in deionized water, and pyridine diazonium salt aqueous solution and potassium iodide were added in an ice bath. After the reaction, the Ti3C2T3C2T3 nanosheets covalently modified with pyridine on the surface were obtained by separation. x Nanosheets, denoted as Py-Ti3C2T x ; (2) Take the obtained Py-Ti3C2T x Dispersed in DMF, then added with fused porphyrin TFP, heated to reflux, and separated to obtain fused porphyrin axially modified Ti3C2T x Nanosheets, namely the target product TFP-Ti3C2T x .

3. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (1), the Ti3C2T x The mass ratio of the nanosheets, pyridine diazonium salt and potassium iodide is 50 mg: (450-550) mg: (0.8-1.2) g.

4. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (1), the pyridine diazonium salt aqueous solution is prepared by the following method: Sodium nitrite and 4-aminopyridine were dissolved in water and hydrochloric acid respectively, and the obtained sodium nitrite aqueous solution and 4-aminopyridine hydrochloric acid solution were cooled to 0° C. in an ice bath; A sodium nitrite aqueous solution cooled to 0° C. is added dropwise to a 4-aminopyridine hydrochloric acid solution to react to obtain a light yellow solution, which is a pyridine diazonium salt aqueous solution.

5. The fused porphyrin axially modified Ti3C2T according to claim 4 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: The ratio of sodium nitrite to water added is (1.2-1.3) g:7 mL; The ratio of the added amount of 4-aminopyridine to the amount of hydrochloric acid is (1.5-1.7) g:5 mL, and the concentration of the hydrochloric acid is 4 mol / L; The mass ratio of sodium nitrite to 4-aminopyridine is (1.2-1.3):(1.5-1.7).

6. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (2), Py-Ti3C2T x The mass ratio of TFP is 1:3~5.

7. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (2), the heating reflux temperature is 115-125°C.

8. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (2), the heating reflux time is 18 to 30 hours.

9. The fused porphyrin axially modified Ti3C2T according to claim 2 x The method for preparing a nonlinear optical nano-hybrid material is characterized in that: In step (2), heating under reflux is carried out under a nitrogen atmosphere.

10. A fused porphyrin axially modified Ti3C2T as claimed in claim 1 x Application of nonlinear optical nanohybrid materials as nonlinear optical materials.

Citation Information

Patent Citations

  • Modifiable hyperconjugation triple molten porphyrin dimer strong two-photon absorption material and preparation thereof

    CN111825684A

  • Triple molten porphyrin dimer covalent functionalized single-walled carbon nanotube nonlinear nano hybrid material and preparation method thereof

    CN112094277A

  • Porphyrin covalently linked molybdenum disulfide nonlinear nano hybrid material as well as preparation and application of porphyrin covalently linked molybdenum disulfide nonlinear nano hybrid material

    CN113735884A

  • Cationic porphyrin functionalized Ti3C2Tx nanosheet nonlinear nano hybrid material as well as preparation and application thereof

    CN113773835A